Find the value of x, if(2 by 3)^-² = (3 by 2)^⁴x (2 by 3)^x​

Question

Find the value of x, if(2 by 3)^-² = (3 by 2)^⁴x (2 by 3)^x​

in progress 0
Maya 2 weeks 2021-09-07T06:31:37+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-07T06:33:19+00:00

    Answer:

    Example 1.

    2×2 – 5x – 12 = 0.

    (2x + 3)(x – 4) = 0.

    2x + 3 = 0 or x – 4 = 0.

    x = -3/2, or x = 4.

    Square Root Principle

    If x2 = k, then x = ± sqrt(k).

    Example 2.

    x2 – 9 = 0.

    x2 = 9.

    x = 3, or x = -3.

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )